Effects of bilateral and unilateral mental practice on actual motor performance and event-related desynchronization - Kazuya Umeno; Yoshihiro Itaguchi (PLoS ONE, 2026)
Bilateral hand movement has been reported to enhance actual motor performance and increase motor cortex activation more than unilateral hand movement. This study investigated the interaction effects of bilateral and unilateral mental practice on event-related desynchronization (ERD) amplitude and unilateral motor performance, to explore better clinical rehabilitation for stroke patients with hemiparesis. The task was a ball rotation, where participants circulated two balls on their palm by using their fingers. Seventy-six healthy young adults were randomly assigned to one of three mental practice groups or a control group without mental practice. In the mental practice groups, three subgroups of participants engaged in ball-rotation motor imagery for two blocks in different orders: bilateral hand imagery followed by left hand imagery (BL group), left hand imagery followed by bilateral hand imagery (LB group), and consecutive left hand imagery (LL group). The results showed greater improvement in actual motor performance in the BL group than in the control group, while the performance of the LB and LL groups did not significantly differ from that of the control group. Greater ERD was observed in the BL group than in the LL group in the early sets of the first block. However, ERD amplitude decreased with continued mental practice, and significant correlations between ERD and motor performance were limited. These results suggest that engaging in bilateral mental practice before unilateral mental practice is beneficial in improving unilateral motor performance. Bilateral mental practice following unilateral mental practice may provide neither notable improvements nor detrimental effects on unilateral motor action. Our findings also reveal a mismatch between ERD and motor performance, implying that these two measures are not straightforwardly linked.